A new Gonamytta katydid from central Mozambique (Orthoptera: Tettigoniidae: Meconematinae) - Guta, Ricardo; Macamo, Laura; Naskrecki, Piotr (Zootaxa, 2021)
A new small predatory katydid Gonamytta deboisselae sp. n. is described from mid-elevation montane forest habitat in central Mozambique; this species is a putative endemic of Mt. Gorongosa. The call of the new species is ultrasonic, with the peak frequency at 38.2 kHz. Anepitacta (A.) scrofina Beier, 1965 is transferred to Gonamytta based on the morphology of the male terminalia.A new small predatory katydid Gonamytta deboisselae sp. n. is described from mid-elevation montane forest habitat in central Mozambique; this species is a putative endemic of Mt. Gorongosa. The call of the new species is ultrasonic, with the peak frequency at 38.2 kHz. Anepitacta (A.) scrofina Beier, 1965 is transferred to Gonamytta based on the morphology of the male terminalia.